Beyond the Mirror Seeing in Art History and Visual Culture Studies - Falkenhausen, Susanne von (Image, 2020)
Since the late 1980s visibility has become a currency of social recognition, and a political issue. It also brought forth a new discipline, visual culture studies, and a hotly contested debate unfolded between art history and visual culture studies over the interpretation of visual culture, whose impact can still be felt today. In this first comparative study Susanne von Falkenhausen reveals the concepts of seeing as scholarly act that underwrite these competing approaches to visuality and society, along with the agendas of identity politics that motivate them. In close readings of key texts spanning from the early 20th century to the present the author crosses expertly between American, German, and British versions of art history, cultural studies, aesthetics, and film studies.